Strategi Ulama Mengantisipasi Penyebaran Hadist Maudhu' di Kecamatan Peureulak - Abd Wahid (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2018)
From the beginning of Islam, hadith maudhu 'or false hadith is a very crucial issue. Prophet Muhammad SAW reminded his Companions through his Hadith